Pulsed current activated combustion synthesis and consolidation of ultrafine NbSi2 from mechanically activated powders - Ko, In-Yong; Kim, Byung-Ryang; Nam, Kee-Seok; Moon, Byung-Moon; Lee, Byung-Soo; Shon, In-Jin (Metals and materials international, 2009)
Dense ultrafine NbSi 2 was synthesized using the pulsed current activated combustion synthesis (PCACS) method within 2 min and in one step from mechanically activated powders of Nb and 2Si. Simultaneous combustion synthesis and densification were accomplished under the combined effects of a pulsed current and mechanical pressure. Highly dense NbSi 2 with a relative density of up to 98 % was produced under simultaneous application of a 60 MPa pressure and a pulsed current. The average grain size and mechanical properties (hardness and fracture toughness) of the compound were investigated.